Invasivmedizin und komplementäre Erkenntnis in der Gegenwartslyrik - Sonja Klimek (Universität Trier, 2019)
How do Germanophone contemporary writers conceive of their poetry in relation to their proper lives and experiences? Comparing two cycles of poems from the beginning of the years 2000 dealing with invasive medical treatments their empirical authors supposedly have undergone themselves – Ulrike Draesner’s „bläuliche sphinx (metal)“ on a missed abortion and Thomas Kling’s „Gesang von der Bronchoskopie“ on a biopsy of the lungs –, this paper explores how poetic language is used to shape and to offer experiences that are staged as escaping entire translation into linguistic propositions, thus claiming a kind of ‘complementary knowledge’ that is conceived as exclusively conveyed, or rather generated, by poetry.